Adaptive backstepping-based tracking control design for nonlinear active suspension system with parameter uncertainties and safety constraints. (May 2019) - Pang, Hui; Zhang, Xu; Xu, Zeren
Abstract: This paper proposes a novel constraint adaptive backstepping based tracking controller for nonlinear active suspension system with parameter uncertainties and safety constraints. By introducing the virtual control input and reference trajectories, the adaptive control law is developed to stabilize both of the vertical and pitch motions of vehicle body using backstepping technique and Lyapunov stability theory, and further to track the predefined reference trajectories within a finite time, which not only ensure the safety performance requirements, but also achieve improvements in riding comfort and handling stability of vehicle active suspension system. Next, the stability analysis on zero dynamics error system is conducted to ensure that all the safety performance indicators are all bounded and the corresponding upper bounds are estimable. Finally, a numerical simulation is provided to verify the effectiveness of the proposed controller and to address the comparability between the classical Barrier–Lyapunov Function based adaptive tracking controller and the proposed controller. Highlights: A novel adaptive backstepping-based tracking controller is developed to stabilize motions of vehicle body and further to track the predefined reference trajectories within a finite time with achieving the improvements in riding comfort and handling stability of vehicle active suspension system. The stability analysis on zero dynamics system is conducted to ensure that all the safety performance indicators are all bounded and the corresponding upper bounds are estimable.